Theatre and creative communication during COVID-19 pandemic: the case of National Kaunas Drama Theatre, Lithuania - Pukelytė, Ina (Creativity Studies, 2023)
The article deals with the questions of digital communication and theatre during the lockdown in 2020–2021. With the example of the National Kaunas Drama Theatre, Lithuania, it is revealed that COVID-19 pandemic forced the cultural sector to experiment and use digital products in new conceptual ways. National Kaunas Drama Theatre proposed their audience an online platform Theatre Onl1ne TV (originally in Lithuanian: Teatras Onl1ne TV), and developed performances which were adapted to the digital environment of the lockdown period: some of the performances were transmitted on Zoom Video Communications platform, especially those for children and adolescents, some of them, such as The Flickering, tested new ways of integrating audiences digitally into theatrical action. The latter performance was created for Facebook users, lasted for four evenings and invited them to become co-creators of the story. The analysis reveals that digital theatre communication attracted audiences of younger generations and can be a useful creative tool in developing a relationship with the new generation of theatre-goers.